Assessment of Risk and Emergency Knowledge Level - Cardiovascular Emergencies in Rural Communities Sungai Nagara, Margasari Village, Tapin, South Kalimantan - Wahid, Abdurahman; Prichoiruna, Hasby; Ainun; Muzakir, Muhamad (Universitas STRADA Indonesia, 2021)
Background Cardiovascular disease contributes to a massive mortality rate in the world and also in Indonesia. Assessment of the risk and level of knowledge of cardiac emergency symptoms needs to be carried out, especially in rural areas where access to cardiovascular treatment is far.Purposes This study aims to assess risk stratification and the level of knowledge. The method of measuring risk and level of knowledge was carried out on 100 Margasari Ilir respondent who were over 40 years old and carried out using the stratified random sampling method during September 2020—measuring risk using the instrument Framingham Risk Score and the level of knowledge using the ACS Response Index.Result The average age of respondents was 54.98 years, 30 men (30%) and 70 women (70%), 22 smokers (22%), seven diabetes mellitus (7%), 11 people ( 11%) had high cholesterol, 41 people (41%) had hypertension, and 33 people (33%) had low HDL levels. The number of people who have a high risk of emergency - cardiovascular emergency is seven people (7%), 24 people are at moderate risk (24%), and 69 people are at low risk (69%). The level of knowledge about cardiac emergencies is in the low category of 80 people (80%), 19 people (19%), and one high (1%).Conclusion It is necessary to increase public knowledge about cardiovascular emergencies.